Trans-Pacific Partnership: History of Gradual Development of Regional Integration in the Asia-Pacific Region - Wan Juntao; D. E. Lyubina (Проблемы постсоветского пространства, 2021)
The Asia-Pacific region today represents an example of deep regional economic integration. This was largely facilitated by the creation of the TRANS-Pacific Partnership. The undisputed advantages of the Trans-Pacific Partnership are the following: opening markets to all member countries, unifying trade rules, removing obstacles to financial cooperation, creating a favorable investment climate and new guarantees to protect small and medium-sized businesses. The analysis of historical stages of creation and development of a such kind of regional association allows us to trace the evolution of economic integration processes and assess the effectiveness and attractiveness of this type of integration. The study of the specifics of the origin of such a large integration Association in Asia is of interest from the point of view of searching for new “growth points” for integration associations in the Eurasian region and in particular in the post-Soviet space.